Efficiency of Bioextract from Fruits Residues towards Green Oak leaf Lettuce Growth - ธุวะคำ ณัฏฐ์วรินท์; ฝั้นเฟือนหา วัชรี (KKU Science Journal, 2019)
The aim of this research was to study the efficiency of bioextract from longan, banana and watermelon residues towards the growth of green oak leaf lettuce. The concentration level of bioextract at 1: 500 (bioextract : water, v/v) was applied every 4-day with triplicate experiments. The results demonstrated that using with bioextract from longan gave the highest leaves number, the leaf length and fresh weight (13.83 leave/plant, 11.38 cm and 82.67 g) respectively. The means of variance (ANOVA) analysis showed that the growth of green oak leaf lettuce was significantly affected by all bioextracts with p<0.05. From the chemical analysis, pH, electrical conductivity (EC), exchangeable potassium (%) obtained from the bioextract of longan was higher than banana and watermelon residues, respectively. Moreover, the available phosphorus (mg/kg) at all bioextracts was lower than 10.00 mg/kg.